Surface Science and Technology - Gong, Shengkai; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Surface Science and Technology is a peer-reviewed and open access journal, aiming to promote the scientific and technological innovations on science, technology and engineering in surface and interface science, and to bridge the transformation of innovations and application in engineering. Surface Science and Technology publishes high-quality review articles, original research papers and letters on the areas of materials, surface and interface, including the following areas, but not limited: Surface & interface physics, chemistry, catalysis, synthesis and energy conversions; Corrosion and protection; Corrosion mechanism Corrosion preventive technology Corrosion-resistant material Coatings and films Friction, wear and lubrication, including tribological surface engineering and application, etc.; Ultra-precision surface machining & metrology; Ultraprecision cutting/grinding Compliant polishing Chemical mechanical polishing/lapping Nanostructured/ultra-smooth surface generation Surface form metrology Subsurface measurement On-machine metrology Functional films; Transparent semiconductor films and devices Hard coatings and anti-reflection protection technology 2D photoelectric materials and devices Ferroelectric films and devices Thermoelectric films and devices Piezoelectric films and devices High entropy alloy films and devices Extreme wetting surfaces Flexible films and devices Intelligent color-changing films and optical modulation films Energy films and devices Sensing and photoelectric detection Functional coatings.
Keywords: Surfaces (Technology).; Thin films; Materials science; Materials; Materials; Catalysis; Force and energy; Nanotechnology; Surfaces, Interfaces and Thin Film; Materials Science; Materials Engineering; Materials for Energy and Catalysis; Nanotechnology